2003
DOI: 10.1097/01.ju.0000061965.51478.79
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Content in Renal Calculi

Abstract: Large endotoxin concentrations can be found in renal infection calculi. Noninfection stones can contain endotoxin but in much lower amounts. Massive endotoxin release could occur with infection stone manipulation, possibly producing increased serum endotoxin concentrations similar to those seen in gram-negative sepsis. Anti-endotoxin strategies may be beneficial in preventing and treating stone induced endotoxemia and the sepsis syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 6 publications
1
39
1
Order By: Relevance
“…Although, this comment is a result of an objective study, our experience showed that in febrile patients even though they are hemodynamically stable, antibacterial treatment may not be required whereas the microbiological evaluation should immediately be done for future management. Sepsis may develop as a result of bacteriemia or endotoxemia after stone or urinary tract manipulation [11] and stimulate inflammatory cascade that can result in septic shock. Septic shock-with up to 66-80% mortality-occurs in 1% of patients following stone manipulation [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…Although, this comment is a result of an objective study, our experience showed that in febrile patients even though they are hemodynamically stable, antibacterial treatment may not be required whereas the microbiological evaluation should immediately be done for future management. Sepsis may develop as a result of bacteriemia or endotoxemia after stone or urinary tract manipulation [11] and stimulate inflammatory cascade that can result in septic shock. Septic shock-with up to 66-80% mortality-occurs in 1% of patients following stone manipulation [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…This is a controversial issue. Even if there is currently no official recommendation as to the use of the UAS during RIRS and there are no guidelines on the correct UAS diameter for the definitive stone sizes, the placement of a UAS could prevent pyelolymphatic and pyelovenous bacterial backflow [5][6][7] with protection from the risk of bacterial dissemination during stone fragmentation. Even if the use of UAS depends on the surgeon's preference, we think that UAS might be considered among the best practices in order to prevent the risk of endotoxin resorption and bacterial dissemination after lithotripsy [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of sepsis is 40-50% if RPUC or stone culture is positive as compared to 25% if previous urine culture was positive and only 14 and 9% if RPUC and stone culture are sterile respectively. However, those who developed SIRS, around half of them had sterile renal pelvic urine and stone culture underscoring the role of endotoxins from dead bacteria in inciting SIRS and sepsis [6,17,18]. …”
Section: Discussionmentioning
confidence: 99%